Pengaruh Tanggapan Di Media Sosial Terhadap Pilihan Koleksi Bagi Pengunjung Interactive Art Museum Bali, Kota Denpasar - Hutama, Gusti Ngurah Kade Wahyu Ari; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2019)
Interactive Art Museum Bali is the new one of tourists attraction in Denpasar City. Although classified as a new tourist attraction, but tourists visit the Interactive Art Museum Bali is always increasing every month. Based on that situation, the research is conducted for analyzing the influence of responses in social media on the collection options for visitors at the tourist attraction of Interactive Art Museum Bali, Denpasar City . The data used in this research is quantitative data. Data analysis techniques used in this study are correlation analysis. The collected data in this study through observation, literature study, questionnaire, and visual material . Informant determination technique used is convenience sampling technique with the number of samples determined by the Slovin formula. The results of this study obtained that the social media used by visitors who come to visit the Interactive Art Museum Bali is Instagram. The influence of responses in social media on collection options for visitors is seen from 3 classifications. First, according to the observing senses, has a correlation analysis of 0653 and 0.598. The second classification is according to the occurrence of having correlation analysis results of 0.627 and 0.668. The third characteristic is according to the environment has the result of correlation analysis of 0.564 and 0.585 .  Keywords: Social Media, Response, Visitor,  Collection,  Interactive Art Museum Bali